Methods for Determining Throughput Capacity of Railway Lines Using Coefficients of Elimination - Čičak, Mirko; Mlinarić, Tomislav Josip; Abramović, Borna (Promet - Traffic&Transportation, 2004)
This work presents the methodological procedure of determiningthe throughput capacity of the railway lines under theconditions of organising traffic with parallel and non-parallelgraphs, i. e. travelling of trains at the same and different speeds.If the non-parallel graph traffic organisation is applied, i. e.trains of different speeds travel along the line, which is often thecase, then the railway line capacity can be calculated by meansof the so-called ’coefficient of elimination’. Therefore, thework defines the coefficient of elimination and presents themethodological approach to its determination for various trafficconditions, i. e. for single-track and double-track lines. Also,some empirical formulas are given which determine the coefficientof elimination.